Influence of cerebral global ischemia-reperfusion on succinate dehydrogenase activity in neurons of different neocortical layers - N. S. Shcherbak; M. M. Galagoudza; D. A. Ovchinnikov; E. O. Shcherbakova; G. U. Yukina; E. R. Barantsevich; V. V. Thomson; E. V. Shlyakhto (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2014)
The aim of the study was to investigate changes in activity of succinate dehydrogenase (SDH) in cytoplasm of neurons of different cortical layers in early and late reperfusion period after global cerebral ischemia in rats. Reversible global cerebral ischemia was modeled by occlusion of the brachiocephalic trunk, left subclavian artery and left common carotid artery for 10 minutes and following reperfusion during 2 or 7 days. The SDH activity in cytoplasm of neurons of II, III and V cortical layers was determined histoenzymatically. It is shown that the SDH activity in neurons of the studied cortical layers was characterized by the increased reperfusion period to the 2 days with a subsequent increased activity of the reperfusion period to the 7 days. The change in the SDH activity in cytoplasm of cortical neurons depends on the particular cerebral layer and duration of postischemic reperfusion.